2007
DOI: 10.1007/s00467-006-0300-6
|View full text |Cite
|
Sign up to set email alerts
|

Decreased cyclosporine exposure during the remission of nephrotic syndrome

Abstract: In this paper, we report the pharmacokinetics changes observed in seven children with steroid-resistant nephrotic syndrome (SRNS). They received cyclosporine A (CsA) microemulsion 6 mg/kg/day and, one week later, they were admitted to perform a 12-h pharmacokinetic profile with eight time sample points. The pharmacokinetic profile was repeated at 24 weeks of treatment, when all patients achieved remission. Blood concentration against time curves were constructed for each patient at weeks 1 and 24 of CsA treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
0
9
0
6
Order By: Relevance
“…To achieve comparable exposures, children require higher relative CSA doses compared to adults. Such differences are mainly caused by shorter intestinal surface absorption and a higher metabolic rate for CSA in children (14,16),. Therefore, adult studies cannot be applied to children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve comparable exposures, children require higher relative CSA doses compared to adults. Such differences are mainly caused by shorter intestinal surface absorption and a higher metabolic rate for CSA in children (14,16),. Therefore, adult studies cannot be applied to children.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that edema, hypoproteinemia, and hypercholesterolemia are involved in CSA bioavailability and clearance (13,16). Hypercholesterolemia is particularly important in CSA-PK because the drug is highly lipophilic and binds to blood cells and plasma proteins; the relative distribution depends on the temperature, drug concentration, hematocrit, and plasma lipoproteins (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nozu et al (2005) reported that 33% of pediatric nephrotic patients present a late peak absorption and discourage the use of C2 as monitoring tool in this population. Our group has recently reported a decrease in CsA exposure in pediatric patients during remission of nephrotic syndrome, suggesting that the target area under the curve (AUC) cannot be the same throughout the treatment (Medeiros et al 2007). At present, CsA dosing regimens are frequently designed according to pharmacokinetic information-derived transplant recipients.…”
Section: Introductionmentioning
confidence: 97%
“…The incidence of CsAN increases the younger the patient is at start of therapy and the longer the duration is [48]. Performing therapeutic drug monitoring in children with FRNS one has to consider that CsA exposure is lower in remission than during relapse [49] due to hyperlipidemia and consecutive lipid binding of CsA. The functional relevance of this finding toward efficacy and toxicity, however, is unclear.…”
Section: Cyclosporinementioning
confidence: 95%